ANALISIS KAPASITAS PRODUKSI PADA LINI PRODUKSI BARU FORD P702 HVPO DENGAN PENDEKATAN METODE ROUGH CUT CAPACITY PLANNING (STUDI KASUS DI PT CSB) - Vera Methalina Afma; Edi Sumarya; Aman Sutrisno (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2021)
ABSTRACTThis research is to analyze capacity requirements and availability on the production line. This research in PT CSB project FORD P702 HVPO production line. Data analysis used the Rough Cut Capacity Planning (RCCP) method by measuring work (time study), forecasting, aggregate planning, master production schedule and capacity analysis with RCCP.Based on research,  standard time is 745 seconds / unit for new prodject FORD P702 HVPO. The best forecasting method  is use Single Moving Average with an MAD error value of 0.04 and MSE error value of 0.021. Aggregate planning calculation results is 27144 units per year with cost of Rp 49,563,348 per year. And the conclusion is the capacity of the FORD P702 HVPO production line is sufficient and feasible to meet customer needs. This research is calculated based on the total production capacity of 19,958,400 seconds per unit in 1 year and the total required capacity of 18,618,775 seconds per unit in 1 year.